2016
DOI: 10.1109/tnsre.2015.2500100
|View full text |Cite
|
Sign up to set email alerts
|

Direction-Dependent Adaptation of Dynamic Gait Stability Following Waist-Pull Perturbations

Abstract: Balance recovery during an unexpected disturbance is a complex motor task, where part of the variability depends on the type of the perturbation itself. Despite of this, little is known to what extent adaptation mechanisms to repeated perturbations are dependent on the direction and the amplitude of the applied disturbances. Here, we used a modified version of the Active Tethered Pelvic Assist Device (A-TPAD) to apply unexpected force-controlled multidirectional waist-pull perturbations while subjects were wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 41 publications
5
30
0
Order By: Relevance
“…This is noteworthy, as it is well documented that mediolateral stability declines with age [6973] and is related to falls incidence in older adults [7477]. Additionally, there is evidence to suggest that adaptations to perturbations in one plane of motion do not necessarily transfer and benefit stability control in other planes of motion [48, 78, 79]. Regarding the type and direction of perturbations used to stimulate adaptation in the reactive recovery responses, it has been previously suggested that, due to the diversity of perturbations that can occur in daily life, it may be more effective to train the mechanisms of stability recovery, rather than focus on specific perturbations [80, 81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is noteworthy, as it is well documented that mediolateral stability declines with age [6973] and is related to falls incidence in older adults [7477]. Additionally, there is evidence to suggest that adaptations to perturbations in one plane of motion do not necessarily transfer and benefit stability control in other planes of motion [48, 78, 79]. Regarding the type and direction of perturbations used to stimulate adaptation in the reactive recovery responses, it has been previously suggested that, due to the diversity of perturbations that can occur in daily life, it may be more effective to train the mechanisms of stability recovery, rather than focus on specific perturbations [80, 81].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, different levels of shoe/floor friction using different materials have been used [87]. As well as trips and slips, a number of various waist push and pull methods have been applied during gait to analyse mediolateral stability in particular [78, 88, 89]. Finally, perturbations involving sudden surface height changes [9092] or multiple changes in surface tilt, height and position [93] have been employed.…”
Section: Discussionmentioning
confidence: 99%
“…They were equal to 15%, 20% and 25% for AP perturbations and 5%, 10%, and 15% BW for ML perturbations. The range of intensity of the perturbations was determined based on previous experiments with healthy young subjects 35 . Before removing the cables, all subjects were exposed to the same set of diagonal perturbations delivered before the training session (TEST POST).…”
Section: Methodsmentioning
confidence: 99%
“…Aprigliano et al used PCA to show that there is no difference in intersegmental coordination patterns between fall-prone older adults and healthy young adults in response to slip-like perturbations [19]. Other studies used PCA of segmental angular momentum to show that the intersegmental coordination patterns observed during recovery from slip-like perturbations are highly correlated with the patterns observed during unperturbed walking [20,21]. Together, these studies suggest that the central nervous system may adopt a preprogrammed and invariant response to perturbation recovery across different tasks and populations.…”
Section: Introductionmentioning
confidence: 99%